2021
DOI: 10.1186/s13690-021-00617-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated failure-time model with weighted least-squares estimation: application on survival of HIV positives

Abstract: Background Survival analysis is the most appropriate method of analysis for time-to-event data. The classical accelerated failure-time model is a more powerful and interpretable model than the Cox proportional hazards model, provided that model imposed distribution and homoscedasticity assumptions satisfied. However, most of the real data are heteroscedastic which violates the fundamental assumption and consequently, the statistical inference could be erroneous in accelerated failure-time model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Loss model based on growing degree days index (𝐿 𝐺𝐷𝐷 ) : The method used to estimate model parameters is the least squares method [16], [17] with the following parameters:…”
Section: Methodsmentioning
confidence: 99%
“…Loss model based on growing degree days index (𝐿 𝐺𝐷𝐷 ) : The method used to estimate model parameters is the least squares method [16], [17] with the following parameters:…”
Section: Methodsmentioning
confidence: 99%
“…Although the Cox PH model is the most common approach for modeling of survival data [9], the accelerated failure time (AFT) model is a more powerful and interpretable model than the Cox PH model provided that the model imposed distribution and homoscedasticity assumption satisfied. It can describe the relationship between the probability of survival and the set of covariates [8]. In addition, the advantage of the parametric AFT approach is that the effect of covariates on survival can be described in absolute terms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent survival analysis study of Mustefa and Chen [8], the researchers had shown that Log-Normal AFT was the best fit shown by AIC. They also concluded that the data were heteroscedastic and indicated that the WLSE method should be used to analyze this data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation